King John - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"King John" by William Shakespeare is a history play written in the mid-1590s about the turbulent reign of King John of England. When France demands John surrender his throne to his nephew Arthur, a succession crisis erupts into war. Amid battles, political betrayals, and papal intervention, loyalties shift between England and France. As nobles defect, family members die, and a foreign prince invades, John faces enemies from all sides$1 (Bincluding threats from within his own kingdom. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_John_(play)
Release date is 1998-10-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: John, King of England, 1167-1216 -- Drama; Great Britain -- History -- John, 1199-1216 -- Drama